A large lung gene expression study identifying fibulin-5 as a novel player in tissue repair in COPD. Issue 1 (2nd July 2014) - Brandsma, Corry-Anke; van den Berge, Maarten; Postma, Dirkje S; Jonker, Marnix R; Brouwer, Sharon; Paré, Peter D; Sin, Don D; Bossé, Yohan; Laviolette, Michel; Karjalainen, Juha; Fehrmann, Rudolf S N; Nickle, David C; et al.
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is a progressive, incurable lung disease characterised by abnormal tissue repair causing emphysema and small airways fibrosis. Since current therapy cannot modify this abnormal repair, it is crucial to unravel its underlying molecular mechanisms. Unbiased analysis of genome-wide gene expression profiles in lung tissue provides a powerful tool to investigate this. Methods: We performed genome-wide gene expression profiling in 581 lung tissue samples from current and ex-smokers with (n=311) and without COPD (n=270). Subsequently, quantitative PCR, western blot and immunohistochemical analyses were performed to validate our main findings. Results: 112 genes were found to be upregulated in patients with COPD compared with controls, whereas 61 genes were downregulated. Among the most upregulated genes were fibulin-5 ( FBLN5 ), elastin ( ELN ), latent transforming growth factor β binding protein 2 ( LTBP2 ) and microfibrillar associated protein 4 ( MFAP4 ), all implicated in elastogenesis. Our gene expression findings were validated at mRNA and protein level. We demonstrated higher ELN gene expression in COPD lung tissue and similar trends for FBLN5 and MFAP4, and negative correlations with lung function. FBLN5 protein levels were increased in COPD lung tissue and cleaved, possibly non-functional FBLN5 protein was present. Strong coexpression of FBLN5, ELN, LTBP2 and MFAP4 in lung tissue and in silico analysis indicated cofunctionality of these genes. Finally, colocalisation of FBLN5, MFAP4 and LTBP2 with elastic fibres was demonstrated in lung tissue. Conclusions: We identified a clear gene signature for elastogenesis in COPD and propose FBLN5 as a novel player in tissue repair in COPD.